Analisis Efisiensi Distribusi Produk pada UMKM Krupuk Jaya Pesona Menggunakan Metode North West Corner (NWC) dan Least Cost (LC) - Fikri Satrio Darmo; Athfal Fuji Dinanda; Bintang Putra Pamungkas (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Product distribution is a crucial element of the supply chain system that ensures the smooth flow of goods from producers to consumers at minimal cost and with high reliability. Distribution efficiency not only reduces operational costs but also improves customer satisfaction, market competitiveness, and business sustainability. In the context of Micro, Small, and Medium Enterprises (MSMEs), distribution efficiency becomes even more critical due to limited financial, human, and infrastructural resources. This study aims to analyze the product distribution efficiency of UMKM Kerupuk Jaya Pesona, located in Cinanggung Village, Serang Regency, Banten Province, by applying two classical transportation methods: the North West Corner (NWC) and Least Cost (LC) methods. Both methods were used to determine the allocation pattern that minimizes total transportation cost across three destination regions: Serang, Cilegon, and Pandeglang. The data include three couriers (as supply sources) and three market destinations (as demands), totaling 18,000 product units per distribution cycle. The results show that both NWC and LC methods yield the same total transportation cost of Rp 358,000,000, although their allocation patterns differ. This indicates that the supply–demand and cost structure of the UMKM’s logistics system is balanced. This research concludes that simple optimization methods such as NWC and LC can serve as practical decision-support tools for MSMEs without requiring complex computational models. The study also recommends the application of the Modified Distribution (MODI) method to verify the optimality of the solution and highlights the importance of logistics efficiency in strengthening MSME competitiveness in the digital era.